A de novo Loss-of-function Variant in RAPGEF6 Supports its Role in Neuropsychiatric Disorders - Simone Treccarichi; Mirella Vinci; Maria Grazia Figura; Antonino Musumeci; Miriam Virgillito; Carla Papa; Valeria Chiavetta; Desiree Brancato; Francesca Bruno; Concetta Federico; Justin Simo; Roberta La Piana; et al. (Journal of Molecular Neuroscience, 2026)
RAPGEF6 is a member of the guanine nucleotide exchange factor (GEF) subfamily that acts on Rap small GTPases and contains a Ras/Rap-associating domain. Although deficiency of this gene has previously been linked to schizophrenia, no MIM phenotype entry currently associates RAPGEF6 with a defined clinical condition. In this study, trio-based whole-exome sequencing (WES) was performed in an individual presenting with psychiatric disorders and mild intellectual disability. WES revealed a de novo frameshift variant, c.272dup (p.Pro92Serfs*6), in the RAPGEF6 gene (NM_016340.6). This variant was classified as likely pathogenic according to ACMG criteria. Nonetheless, the contribution of additional genetic factors not detected by WES cannot be excluded. According to developmental transcriptomic data from the BrainSpan database, RAPGEF6 is expressed in the human brain across the entire lifespan and participates in neuron projection development, Rap-protein signal transduction, and regulation of GTPase activity. Structural variation data from DECIPHER further indicate that copy-number variants involving RAPGEF6 are primarily associated with intellectual disability and micrognathia. In addition, DECIPHER shows that RAPGEF6 is highly intolerant to loss-of-function (LoF) variants. Both NMD-Esc predictor and Mutation Taster suggest that the identified frameshift mutation is likely to trigger nonsense-mediated decay (NMD) of the RAPGEF6 transcript, resulting in loss of protein production. In addition, RAPGEF6 expression progressively increased during retinoic acid-induced neuronal differentiation of SK-N-BE neuroblastoma cells, supporting a potential role of this gene in neuronal maturation processes. Together, these data support a contributory role of RAPGEF6 haploinsufficiency in neurodevelopmental and psychiatric phenotypes, reinforcing its emerging relevance in neuropsychiatric disorders.

Wildfire ash undermines the physiology of the Mediterranean coral Cladocora caespitosa - Enrico Montalbetti; Davide Seveso; Simone Farina; Simone Bava; Elisa Carta; Laura Castellano; Paolo Galli; Valerio Isa; Yohan Didier Louis; Rossana Marzaioli; Davide Moccia; Stefania Papa; et al. (Marine Environmental Research, 2026)

Pseudotachylytes in felsic lower-crustal rocks of the Calabrian Serre massif: A record of deep- or shallow-crustal earthquakes? - Simone Papa; Giorgio Pennacchioni; Alfredo Camacho; Kyle P. Larson (Lithos, 2023)